OPTIMIZING MEDICAL EDUCATION FOR CLINICAL STUDENTS DURING COVID-19 PANDEMIC: A LITERATURE REVIEW - Patricia Budimulia; Andree Kurniawan (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2021)
Background: COVID-19 pandemic has impacted numerous of matters and medical education is one of them. It is crucial to dissect measures that could be taken to optimize medical education for clinical students during COVID-19 pandemic. There is still limited evidence or data on how to approach this situation. The aim of this literature review is to unfold guidance on optimizing medical education for clinical students during COVID-19 pandemic.Methods: The literature was searched by accessing the PubMed, PubMed Central, and Google Scholar databases. Literature search was conducted from December 1, 2019 to April 24, 2020, using the key words of “medical education”, “clinical students OR clerkship students”, “covid-19”.Results: Based on the literature search, 20 literatures related to medical education of clinical students during COVID-19 pandemic were obtained. Institutions have taken a differing approach during COVID-19 pandemic. Implementing teleteaching, creating an integrated learning environment, strategies to improve role models, telemedicine, training programs and psychological support are approaches in order to optimize medical education for clinical students during COVID-19 pandemic.Conclusion: Institutions had to instantly alter medical education during COVID-19 pandemic. The lives of many students have been hugely impacted in terms of financial, psychological, delay in graduation, uncertainty, residency application and clinical placements. There are ways in which technology can ease some of these problems, albeit not fully resolving all these issues. Therefore, it is still crucial to further shine a light on how to optimize medical education during this unprecedented time.